Предмет:
МатематикаАвтор:
анонима) ab2 + cd2 - ad2 - b2c = ab2 - ad2 + cd2 - b2c = a(b2 - d2) + c(d2 – b2) = a(b2 - d2) - c(b2 - d2) =
= (b2– d2)(a – c) = (b – d)(b + d)(a – c).
б) x2y2 + 1 - y2 - x2 = x2y2 - x2 - y2 + 1 = x2(y2 - 1) – y2 + 1 = х2(у2 - 1) - (у2 - 1) = (у2 - 1)(х2 -1) =
= (у - 1)(у + 1)(х - 1)(х +1).
Автор:
alyssaaisaДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть